Unhealthy alcohol use in older adults: Association with readmissions and emergency department use in the 30 days after hospital discharge. (1st January 2016) - Chavez, Laura J.; Liu, Chuan-Fen; Tefft, Nathan; Hebert, Paul L.; Clark, Brendan J.; Rubinsky, Anna D.; Lapham, Gwen T.; Bradley, Katharine A.
Highlights: Evaluated the association of unhealthy drinking with 30-day readmissions. Unhealthy drinking identified through routine outpatient alcohol screening. High-risk drinking associated with 1% greater absolute risk for 30-day readmissions. Other social risk factors appeared to account for this elevated risk. Abstract: Background: Unhealthy alcohol use could impair recovery of older patients after medical or surgical hospitalizations. However, no prior research has evaluated whether older patients who screen positive for unhealthy alcohol use are at increased risk of readmissions or emergency department (ED) visits within 30 days after discharge. This study examined the association between AUDIT-C alcohol screening results and 30-day readmissions or ED visits. Methods: Veterans Affairs (VA) patients age 65 years or older, were eligible if they were hospitalized for a medical or surgical condition (2/1/2009–10/1/2011) and had an AUDIT-C score documented in their VA electronic medical record in the year before they were hospitalized. VA and Medicare data identified VA or non-VA index hospitalizations, readmissions, and ED visits. Primary analyses adjusted for demographics, comorbid conditions, and past-year health care utilization. Results: Among 579, 330 hospitalized patients, 13.7% were readmitted and 12.0% visited an ED within 30 days of discharge. In primary analyses, high-risk drinking ( n  = 7, 167) and nondrinking ( n  = 357, 086) were associated with increased probability of readmission (13.8%, 95% CI 13.0–14.6%; and 14.2%, 95% CI 14.1–14.3%, respectively), relative to low-risk drinking (12.9%; 95% CI 12.7–13.0%). Only nondrinkers had increased risk for ED visits. Conclusions: Alcohol screening results indicating high-risk drinking that were available in medical records were modestly associated with risk for 30-day readmissions and were not associated with risk for ED visits.